2008
DOI: 10.21273/hortsci.43.7.2039
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity and Phenolic Antioxidants of Midwestern Black Raspberries Grown for Direct Markets Are Influenced by Production Site

Abstract: Black raspberries (Rubus occidentalis L.) are rich in phytonutrients that have demonstrated chemoprotective properties against certain degenerative diseases. To estimate variability in phytonutritional quality among sources of black raspberry, 19 samples representing four common midwestern cultivars obtained from eight production sites were assayed for their antioxidant capacity [2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing ability of plasma (FRAP) methods], total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
45
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 36 publications
13
45
1
1
Order By: Relevance
“…TACY as measured by the pH differential method were lower than total anthocyanin by HPLC/DAD, but measurements were significantly correlated (Spearman rank order correlation R = 0.68, p 6 0.05) as previously demonstrated (Lee & Finn, 2007;Lee, Rennaker, & Wrolstad, 2008). Moreover, values of TACY by pH differential were similar to or slightly lower than those reported by others (Moyer et al, 2002;Ozgen et al, 2008;Wang & Lin, 2000;Wang & Zheng, 2005), ranging from 141 to 627 mg 100 g À1 (n = 31; from 'Earlysweet', 'Munger', 'Jewel', 'Haut', 'MacBlack', and 'Bristol'; all previously reported values by others were converted and expressed as cyanidin-3-glucoside). Total anthocyanins by HPLC in this study were somewhat lower than reported by Wu et al (2006), 687 mg 100 g À1 (n = 1; cultivar unknown), and Hager et al (2008), 1113 mg 100 g À1 (n = 1; 'Munger').…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…TACY as measured by the pH differential method were lower than total anthocyanin by HPLC/DAD, but measurements were significantly correlated (Spearman rank order correlation R = 0.68, p 6 0.05) as previously demonstrated (Lee & Finn, 2007;Lee, Rennaker, & Wrolstad, 2008). Moreover, values of TACY by pH differential were similar to or slightly lower than those reported by others (Moyer et al, 2002;Ozgen et al, 2008;Wang & Lin, 2000;Wang & Zheng, 2005), ranging from 141 to 627 mg 100 g À1 (n = 31; from 'Earlysweet', 'Munger', 'Jewel', 'Haut', 'MacBlack', and 'Bristol'; all previously reported values by others were converted and expressed as cyanidin-3-glucoside). Total anthocyanins by HPLC in this study were somewhat lower than reported by Wu et al (2006), 687 mg 100 g À1 (n = 1; cultivar unknown), and Hager et al (2008), 1113 mg 100 g À1 (n = 1; 'Munger').…”
Section: Resultssupporting
confidence: 79%
“…Based on an extracted ion chromatogram of 449.2, minor amounts of cyanidin-3-glucoside were detected. Ozgen et al (2008) found only minor differences in anthocyanin content (measured by pH differential) between the cultivars 'Bristol', 'Jewel', 'MacBlack', and 'Haut', particularly in comparison with differences found among eight different production sites in Ohio (USA). Our data show somewhat larger differences between samples at a single location, however this should be expected with the greater diversity in samples.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Previous studies (e.g. Connor et al, 2005a,b;Ö zgen et al, 2008) reported strong relationships among measures of TP content, anthocyanin levels, and antioxidant capacity of Rubus species. From our data we calculated high correlation coefficients (r) between the TP values of red raspberry samples and their respective antioxidant capacities.…”
Section: Resultsmentioning
confidence: 86%
“…However, phenolic compounds and antioxidant capacities can be influenced, mainly by genetics and environment (Anttonen and Karjalainen, 2005;Connor et al, 2005a,b;McGhie et al, 2002;Ö zgen et al, 2008). Furthermore, Connor et al (2005a) indicated that having high bioactive compounds variability among the accessions is important to obtain superior cultivars, and selection programs are the important resources.…”
Section: Introductionmentioning
confidence: 99%